Stres a radzenie sobie z łuszczycą. Badania empiryczne - Stojda, Anna (My University, 2012)
Praca ma charakter teoretyczno-empiryczny. Podjęty problem badawczy dotyczy stresu i radzenia sobie ze stresem choroby jaką jest łuszczyca. Badaniami objęto grupę 50 chorych na łuszczycę (24 kobiety i 26 mężczyzn), w przedziale wiekowym od 18 do 60 roku życia. W badaniach wykorzystano kwestionariusz ankiety własnej konstrukcji. Zebrane dane empiryczne poddano analizie ilościowej i jakościowej. Z przeprowadzonych analiz wynika, że osoby chore na łuszczycę nie akceptują własnej choroby. Czują się izolowane od otoczenia. Zgłaszają problemy interpersonalne, których przyczynę upatrują w braku wiedzy otoczenia na temat choroby łuszczycy. Osoby badane unikają kontaktu z bliskimi i otoczeniem, uciekają od sytuacji stresowych zamykając się w sobie. Uzyskane wyniki przekonują o celowość pomocy psychologicznej skierowanej do osób chorych na łuszczycę. Takie postępowanie może okazać się pomocne w przystosowywaniu osoby do okoliczności choroby i poprawy jakości życia.

The work has a theoretical and empirical character. Aresented problem concerns stress and cope with stress that is the psoriasis disease. The research included a group of 50 patients who suffering the psoriasis disease (24 women and 26 men), in the age group from 18 to 60 years old. In the study was used a questionnaire survey of on diborated own structure. The empirical data collected were analysed quantitatively and qualitatively. From the analyses carried out, it appears that the persons suffering the psoriasis disease don’t accept their own disease. They feel isolated from is surroundings. They report interpersonal problems, which cause they attribute in the absence of an ambient on the psoriasis disease. The persons examined shall avoid contact with loved ones and their surroundings, with confidence from pressure by closing in itself. The results obtained on the desirability of psychological assistance addressed to convince people sick on the psoriasis disease. Such proceedings may prove helpful in adaptation of the person to circumstances’ of the disease and improvement of the quality of life.
Stress and coping with psoriasis. Empirical studies
Keywords: stres; choroby; psychologia; ankieta